Pendampingan Pemanfaatan Digital Marketing Berbasis Media Sosial Untuk Mempertahankan Stabilitas Penjualan Pada UMKM - Fitrianingsih Fitrianingsih; Eka Mayastika Sinaga; Sarwoto Sarwoto; Benhart Nainggolan; Dedy Dwi Arseto; Nada Nabilah (Digital Business Progress, 2026)
Digital transformation has encouraged micro, small, and medium enterprises to adapt technology-based marketing strategies to maintain business competitiveness. This community service activity aims to improve the digital competence of MSMEs through mentoring the use of social media as a marketing tool to maintain sales stability and expand market reach. The activity was carried out on 20 MSMEs in Pelita Village through stages of observation, training, direct practice, and evaluation. The results of the activity showed an increase in the use of business accounts from 30% to 85%. The level of participant satisfaction with the program reached 90%, which indicates that the practice-based mentoring model has high effectiveness in increasing the digital marketing capacity of MSMEs. These findings indicate that the use of social media-based digital marketing can be an effective strategy in supporting business sustainability and strengthening the local economy. Keywords: MSMEs, Digital Marketing, Brand.